Processing and rheological behavior of cross‐linked polyethylene containing disulfide bonds. (3rd December 2021) - Montoya‐Ospina, Maria Camila; Verhoogt, Henk; Osswald, Tim A.
Abstract: Vitrimers are a new class of materials that consist of chemically cross‐linked networks that engage in thermoactivated associative exchange reactions. These exchange reactions can impart malleability, healing, and recyclability properties to thermosets. In this study, a one‐step protocol to prepare linear low‐density polyethylene (LLDPE) vitrimer‐like materials with disulfide exchange bonds via reactive blending is presented. The cross‐linking reaction of maleic anhydride‐grafted‐linear low‐density polyethylene (LLDPE‐MAH) and 4, 4′‐dithiodianiline was followed in a torque rheometer. The degree of MAH‐functionalization and its impact on the melt rheology, dynamic mechanical properties, and thermal properties of the vitrimer was studied. The cross‐linked LLDPE possessed a mostly elastic behavior, with storage modulus ( G ′ ) higher than loss modulus ( G ′ ′ ) in the entire frequency range. The complex viscosity of cross‐linked LLDPE at high frequencies (>100 rad/s) was comparable to the thermoplastic LLDPE. The MAH‐groups and formation of cross‐links decreased the degree of crystallinity, which led to a decrease in the storage modulus at a temperature of 35°C. The storage modulus and dimensional stability of the materials improved with cross‐linking density, suggesting potential benefits of LLDPE vitrimers in secondary manufacturing processes. Finally, the reprocessing ability was demonstrated via internal mixing and the rheological and mechanical properties were retained. Abstract :